Bacterial Diversity of the Corpses - Ahmet Asan (European Journal of Biology)
The study presents the importance of forensic bacteriology, its use in forensic cases, the methods for bacteriological sampling from corpses, the types and species of bacteria isolated from human and pig corpses, which are most commonly used in forensic biology. The microbial changes that occur after death remain unclear. Postmortem microbiology is a relatively new field of research. After death, the failure of the immune system and other physical barriers leads to the proliferation and spread of microbes. In order for bacteriological information to be accepted within the scope of forensic bacteriology, the court must find suspicion to be present about whether the bacteria seen on the body will contribute to solving the case. Experts must be appointed to examine the issue in line with this suspicion, and these experts must prepare and submit their reports to the court at the requested time. When considering the literature studies, forensic bacteriology has been suggested to be a scientific discipline in the developmental stage and to only be able to provide circumstantial evidence in forensic cases as opposed to primary evidence. According to the literature review, most bacterial studies isolated from corpses were conducted in Romania. Although bacterial samples were isolated from various parts of the corpses, bacteria were mostly isolated from their blood samples. According to literature searches from various scientific journal databases, no study has occurred with a list of the bacteria isolated from corpses. This study is thought to be able to fill this important gap.